Comparison of the optical properties of pre-colored dental monolithic zirconia ceramics sintered in a conventional furnace versus a microwave oven - Kim, Hee-Kyung; Kim, Sung-Hun (The journal of advanced prosthodontics, 2017)
The purpose of this study was to compare the optical properties of pre-colored dental monolithic zirconia ceramics of various thicknesses sintered in a microwave and those in a conventional furnace. A2-shade of pre-colored monolithic zirconia ceramic specimens (22.0 mm × 22.0 mm) in 3 thickness groups of 0.5, 1.0, and 1.5 mm were divided into 2 subgroups according to the sintering methods (n=9): microwave and conventional sintering. A spectrophotometer was used to obtain CIELab color coordinates, and translucency parameters and CIEDE2000 color differences (Δ ) were measured. The relative amount of monoclinic phase (X ) was estimated with x-ray diffraction. The surface topography was analyzed by atomic force microscope and scanning electron microscope. Statistical analyses were conducted with two-way ANOVA (α=.05). There were small interaction effects on CIE *, *, and TP between sintering method and thickness ( <.001): * (partial eta squared η =0.115), * (η =0.136), and TP (η =0.206), although higher * values were noted for microwave sintering regardless of thickness. Color differences between two sintering methods ranged from 0.52 to 0.96 Δ units. The X values ranged from 7.03% to 9.89% for conventional sintering, and from 7.31% to 9.17% for microwave sintering. The microwave-sintered specimen demonstrated a smoother surface and a more uniform grain structure compared to the conventionally-sintered specimen. With reduced processing time, microwave-sintered pre-colored dental monolithic zirconia ceramics can exhibit similar color perception and translucency to those by conventional sintering.